Alpha‐fetoprotein‐adjusted‐to‐HCC‐size criteria are associated with favourable survival after liver transplantation for hepatocellular carcinoma. Issue 2 (10th February 2021) - Meischl, Tobias; Rasoul‐Rockenschaub, Susanne; Győri, Georg; Scheiner, Bernhard; Trauner, Michael; Soliman, Thomas; Berlakovich, Gabriela; Pinter, Matthias
Abstract: Background: The Milan criteria are recommended to select hepatocellular carcinoma (HCC) patients for liver transplantation (LT). The utility of other selection criteria, such as the alpha‐fetoprotein‐adjusted‐to‐HCC‐size (AFP‐UTS) criteria, is still unclear. Objective: We investigated, in HCC patients who underwent LT, the survival and the recurrence after LT according to AFP‐UTS and Milan criteria, the impact of early recurrence and the correlation between radiological and pathological staging. Methods: Adult HCC patients undergoing deceased donor LT at the Medical University of Vienna between 1997 and 2014 were retrospectively analysed. Results: Among 166 patients included, the number of patients who fulfilled Milan or AFP‐UTS criteria was the same (139 [84%] each), although not all of them were the same individuals; 127 patients (77%) fulfilled both Milan and AFP‐UTS criteria. Median overall survival of patients within AFP‐UTS was 126.9 versus 34.2 months outside AFP‐UTS (5‐year survival rate 71% vs. 43%; p  = 0.104). The 5‐year recurrence rate was significantly lower in patients fulfilling the AFP‐UTS criteria (18%) than in those exceeding AFP‐UTS (64%; p  < 0.001). Of the 139 patients within Milan criteria on imaging, 24 (17%) had microvascular invasion and 47 (34%) were outside Milan according to explant histology. Early recurrence correlated with AFP‐UTS and was associated with dismal survival (median overall survival 17.2 vs. 122.1 months, p  = 0.002). Conclusions: The overall survival of patients within AFP‐UTS criteria was favourable with a 5‐year survival rate above 70%. Early recurrence is associated with worse survival after LT. The AFP‐UTS criteria may be more suitable to exclude patients at high risk of (early) recurrence than Milan criteria.